Diversity and genetic structure of natural populations of the palm tree Euterpe precatoria (Arecaceae) - dos Santos Cochev, Jackeline; Encinas Dardengo, Juliana de Freitas; Bandini Rossi, Ana Aparecida; Souza Rodrigues, Alex; Vicente Tiago, Auana; Moreno de Pedri, Eliane Cristina; Muller Zortea, Kelli Evelin; Gonçalves Garcia, Magali; Alves da Silva Neves, Sandra Mara (Revista de Biología Tropical, 2022)
Introduction: The natural ecosystems of northern Mato Grosso, Brazil, are in process of fragmentation, mainly due to population growth and the expansion of agriculture. This endangers the palm Euterpe precatoria (locally known as açaí), used for construction, palm hearts, juices and ice cream. Objective: To evaluate the local diversity and genetic structure in native populations of E. precatoria. Methods: We collected leaves from 106 fruiting palms from five populations in Mato Grosso State, for analysis of microsatellite markers with Polymerase Chain Reaction. Results: The five SSR loci revealed a total of 30 alleles, ranging from 5 (EE23 and EE43) to 7 (EE2 and EE15), with an average of 6 alleles per locus. The mean PIC was 0.74 and confirmed low heterozygosity and inbreeding. The UPGMA dendrogram produced two groups and molecular variance revealed greater genetic differentiation within populations. The high levels of homozygous microsatellite loci indicate low genetic diversity. Conclusions: These populations have low gene diversity, high average number of alleles per locus, and rare and exclusive alleles. We recommend the establishment of permanent conservation units with corridors among them.